DESIGN MATHEMATICS PROBLEM SOLVING TASKS : STUDENTS RESPONSE - Hartatiana Hartatiana; Ambarsari Kusuma Wardani (UNIVERSITAS MUHAMMADIYAH METRO, 2021)
Problem solving is an important part of learning mathematics, but the problem solving ability of students in Indonesia is still low. This study develops problem solving tasks in an Islamic context for junior high school students. Practicality was obtained through test questions on one-to-one and small groups of 22 (twenty two) students from several cities in Indonesia as well as analysis of student work results, questionnaires and interviews. The results of data analysis indicate that practicality Islamic context problem tasks have been obtained and have high validity and reliability so that the questions are feasible to use.